INNOVATIVE FINANCIAL FEATURES IN THE REGION - Ibodov Jamshid Koyli oglu (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
The article analyzes the essence, historical origin, characteristics and functions of finance. The monetary relations, distribution and fund-based features of finance are highlighted. The views of various economists on the functions of finance (distribution, control, incentive) are presented. The manifestation of financial relations at the macro and micro levels is shown.